Le perifrasi modali in siciliano actico - Núñez Román, Francisco (Philologia Hispalensis, 2007)
RESUMEN Este trabajo estudia las perífrasis modales del dialecto siciliano antiguo (siglos XIII- XV) sobre un corpus habitualmente poco considerado: textos de carácter no literario. Tras la identificación de las diversas estructuras perifrásticas modales existentes en los textos seleccionados, el análisis de las mismas revelará cómo el siciliano antiguo contaba ya con un sistema perifrástico perfectamente consolidado y bien estructurado para la expresión de los diversos valores modales, además de presentar determinadas construcciones perifrásticas existentes en otras lenguas romances pero cuyos valores modales no han sobrevivido en siciliano moderno. ABSTRACT This work studies the modal periphrasis in ancient Sicilian dialect, from the 13 th to 15th centuries, based on a rarely considered corpus: non literary texts. After identifying the several modal periphrastic structures found in the selected texts, their analysis will reveal that the ancient Sicilian dialect already had a perfectly consolidated and well-structured periphrastic system for expressing the different modal meanings. Furthermore, the ancient Sicilian dialect presents certain periphrastic constructions existing in other romance languages but whose modal meanings have not survived in the modern Sicilian language.